2022
DOI: 10.1177/21501319211073415
|View full text |Cite
|
Sign up to set email alerts
|

A Situation Assessment of Community Health Workers’ Preparedness in Supporting Health System Response to COVID-19 in Kenya, Senegal, and Uganda

Abstract: Background: Coronavirus disease (COVID-19) caused socio-economic disruptions across the globe. The pandemic disrupted the health system (HS) calling for reengineering in response to high infection rates, deaths, and resultant containment measures. To deal with COVID-19 and promote resilience, community health workers (CHWs) were engaged across countries. Objective: Assess the preparedness of CHWs in supporting health system response in prevention and management of COVID-19 in Kenya, Senegal, and Uganda. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Our synthesis showed that apart from routine service delivery CHWs were actively involved in COVID-19 activities such as contact tracing, community education and awareness on COVID-19, screening people with potential COVID-19 symptoms, counselling migrants. Similar roles in both the COVID-19 response and continued delivery of routine services during COVID-19 have been identified by other research, both in some countries included in our research, such as India, Sierra Leone and Kenya and in other contexts, as well as in global syntheses [8,16,18,22,[83][84][85].…”
Section: The Ever-expanding Role Of the Chwsupporting
confidence: 72%
“…Our synthesis showed that apart from routine service delivery CHWs were actively involved in COVID-19 activities such as contact tracing, community education and awareness on COVID-19, screening people with potential COVID-19 symptoms, counselling migrants. Similar roles in both the COVID-19 response and continued delivery of routine services during COVID-19 have been identified by other research, both in some countries included in our research, such as India, Sierra Leone and Kenya and in other contexts, as well as in global syntheses [8,16,18,22,[83][84][85].…”
Section: The Ever-expanding Role Of the Chwsupporting
confidence: 72%
“…In this context, CHWs had little access to external support and training [ 36 ]. Similarly, in a mixed methods study Chengo et al document CHW household visits in Kenya, Uganda, and Senegal during the COVID-19 pandemic [ 8 ]. Chengo et al also highlight key challenges experienced by CHWs including the lack of protective gear, training, and reporting tools that were addressed by the intervention in Siaya County [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data from India, Bangladesh, Pakistan, Sierra Leone, Kenya and Ethiopia, document the important role CHWs played in surveillance, community education and support of community members with COVID-19 [ 7 ]. An assessment of CHW preparedness in Kenya, Senegal, and Uganda by Chengo et al found, however, that CHWs faced significant challenges because of the lack of training and personal protective equipment (PPE) [ 8 ]. Other studies demonstrated that training, especially of rural CHWs, led to improved COVID-19 surveillance efforts and reduced COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigated the mental health of healthcare providers, demonstrating considerable levels of mental exhaustion during the COVID-19 pandemic [8][9][10][11]. However, few studies addressed the effects of the pandemic on the mental health of remote and on-site general workers over time [12,13].…”
mentioning
confidence: 99%